PROBABILITAS IJMA’ DI ERA MODERN (IMPLIKASI PERBEDAAN DEFINISI, SYARAT DAN RUKUN TERHADAP KEMUNGKINAN TERJADINYA IJMA’, KEDUDUKAN DAN HUJJAHNYA) - Adin Fadilah (Al-Majaalis : Jurnal Dirasat Islamiyah, 2016)
Ijma 'is one of the arguments of Personality' that has the force of argument under the Koran and Hadith, ijma 'is the first proposition after the al-Quran and Hadith that can be used as guidelines in exploring the laws of Personality'. However there are some Muslim community which does not recognize the existence of ijma 'where they are only based on the Quran and al-Hadith, their diligence in itself likely will not be separated from the two text itself. Variation ijma> 'The dimungkinakan for their differences as well as the definition of halal berkaiatan with ijma>' such terms, pillars and so on. From this study we can conclude that: On the issue of ijma> 'happen perbeadaan opinion among the scholars. The differences are due to differences in the definition of the ulama ijma> '. Selaian, differences in the terms and the pillars of the proposed menajadi importance in understanding ijma> '. The most fundamental thing ijma’ is a difference whether the agreement that all or the majority of scholars only. In this case the author is more inclined to the latter opinion. Both now it is not improbable occurrence of Ijma> '. Although it uses the most stringent requirements. Due to technological advances, create obstacles distance between the scholars are not a barrier anymore. However, the difficulty is that everyone has a different opinion in accordance with the experience and knowledge he possessed.